The Influence Of Profitability, Liquidity, Asset Structure, And Company Size On Capital Structure Pharmaceutical Companies In The Covid-19 Pandemic - Ilmiyati, Ismi; Muniroh, Hetty (Badan Penerbit Universitas Muria Kudus, 2023)
The purpose of the research to be conducted is to determine the effect of profitability, liquidity, asset structure, and company size on the capital structure of pharmaceutical companies during the Covid-19 pandemic. Researchers used the documentation method, the entire population of 12 pharmaceutical companies listed on the Indonesia Stock Exchange after being outliers became 9 companies, 5 years of research from 2017-2021. Data analysis techniques using the classical assumption test, descriptive statistics, multiple linear regression analysis, t test and test the coefficient of determination. The conclusion of the research results is that profitability, liquidity, and firm size have a significant negative in accordance with the direction of the hypothesis, while the asset structure is not in accordance with the direction of the first hypothesis, with the final result having a significant negative.